Research patterns in sports law and sports governance: a scopus bibliometric study - Kamenecka-Usova, M.; Korde, Z.; Zidens, J.; Luika, S.; Agapova, O.; Palkova, K.; Martinsone, K. (Frontiers in Sports and Active Living, 2025)
This bibliometric study explores research patterns in lex sportiva, sports law and sports governance, analyzing data retrieved from Scopus between 1977 and 2024. The study examines publication trends, citation networks, keyword co-occurrence and the most influential sources to identify key themes, leading authors and reputable journals. The results indicate that while both fields have been extensively studied, their intersection remains relatively underexplored, with "good governance" emerging as the primary link between sports law, lex sportiva, and governance studies. The citation analysis highlights regional disparities, with Australia, the United States, and the United Kingdom leading in research impact, while countries such as China and Germany exhibit high output but lower citation influence. Co-authorship networks reveal strong collaborations within Europe and North America but limited engagement from other regions. The findings underscore the growing importance of sports governance and legal frameworks in addressing contemporary challenges, particularly within the European Sport Model. This study provides valuable insights for researchers and policymakers, emphasizing the need for interdisciplinary approaches to further advance the field.